Macro-level factors explaining inequalities in expected years lived free of and with chronic conditions across Spanish regions and over time (2006-2019) - Elisenda Rentería; Pilar Zueras (Elsevier, 2022)
Life expectancy has long been associated with macro-level factors, including health expenditures, but little research has focused on the relationship with morbidity measures. This paper examines the relationship between the expected years lived free of and with chronic conditions (YLFCC and YLCC) at age 50 and macroeconomic and social factors including, for the first time, several indicators of public health expenditure. We calculate YLFCC and YLCC for Spanish regions using the Sullivan method over a long period of time (2006-2019). Spain is a good case study due to two reasons. First, its national health system is decentralized among regional administrations since 2002. Second, the financial crisis of 2008 led to public health cuts in 2010-2014 that each region handled differently. We use fixed-effects models to assess the relationship between changes in macro-level regional indicators (socioeconomic factors, healthcare resources, health behavior and public health expenditures) with YLFCC and YLCC across regions and over time. Results show that socioeconomic levels, public health expenditure, healthcare resources and health behaviors are associated with years lived free of and with chronic conditions when analyzing them independently. However, in the global model including all these dimensions only public health expenditure is associated with both YLFCC and YLCC for men and women, showing that a higher level of expenditures is correlated with more YLFCC and less YLCC. Therefore, regional authorities need to pay special attention to the level of investments on health services, as they are clearly associated with a better quality of living of the middle age and older population.